Red Sports Culture Integrated into Ideological and Political Education in Colleges and Universities Value Characteristics and Implementation Path - Liu, Feifei; Liu, Rongde; Huang, Xiaoying; Luo, Changxin; Mi, Zuwei (Quality in Sport, 2025)
Purpose: This study focuses on exploring how the red sports culture is integrated into the ideological education of colleges and universities. Methodology: The main method used in this study was logical analysis as a way to ensure the successful implementation of this study. Findings: Red sports culture refers to the sports and cultural activities led by the Communist Party of China. Red sports culture has gone through three stages: germination, basic establishment and further growth. Its survival conditions need to have certain political guarantee, material foundation, practical foundation and theoretical cornerstone. It is characterized by the spirit of patriotism, the spirit of revolution, and the spirit of practice. Its role is to enrich the content of ideological education in colleges and universities, to strengthen the ideology of ideological education in colleges and universities, and to cultivate a team of talents who are“morally, intellectually, physically, socially and aesthetically”qualified. Value: This study proposes a specific implementation path for better integrating the red sports culture into the ideological and political education in colleges and universities.